HISTORICAL INFORMATION ABOUT UZBEK EMBROIDERY (World Bulletin of Social Sciences, 2022)
The author of this article, based on the analysis of archaeological and written sources, shows the development of Uzbek national embroidery from ancient times to the end of the Middle Ages. The article also shows the nature of transformation processes in the field of national embroidery.